Assessment of Heavy Metal Contamination in Paddy Field Soils: A Case Study in Ranau Valley, Sabah, Malaysia - Ahmad Damanhuri Nadrah; Harun Siti Norliyana; Abd Rahim Sahibin (E3S Web of Conferences)
The weathering of ultrabasic rocks surrounding the Ranau Valley in Sabah, Malaysia, contributes to the formation of soils with elevated concentrations of heavy metals. These metals, including Manganese (Mn), Nickel (Ni), Chromium (Cr), and others, have the potential to disperse into nearby paddy fields, leading to significant soil contamination. This study aims to: (a) determine the concentrations of heavy metals in the paddy field soils of Ranau Valley and (b) map their spatial distribution using Geographic Information System (GIS) technology. The results revealed that Mn was the most abundant metal, with concentrations reaching 13,855.67 mg/kg, followed by Iron (Fe), Ni, Zinc (Zn), and Cr. Several metals, including Mn, Ni, and Cr, exceeded established soil toxicity thresholds, particularly in areas influenced by ultrabasic rocks and agricultural practices. Elevated levels of Copper (Cu), Lead (Pb), Zn, and Cadmium (Cd) were also observed in regions affected by the use of chemical fertilizers. These findings highlight the potential risks to agricultural productivity and food safety in the region, as metals such as cadmium and lead can accumulate in crops, posing health risks to local populations. To address these concerns, remediation strategies such as organic amendments and pH adjustments are recommended. Regular monitoring and sustainable soil management practices will be essential to safeguard soil health, ensure food security, and reduce environmental risks in the Ranau Valley.